Distinct diurnal chemical compositions and formation processes of individual organic-containing particles in Beijing winter. (1st February 2023) - Ma, Tao; Furutani, Hiroshi; Duan, Fengkui; Kimoto, Takashi; Ma, Yongliang; Zhu, Lidan; Huang, Tao; Toyoda, Michisato; He, Kebin
Abstract: Organic aerosols (OA) are major components of fine particulate matter, yet their formation mechanism remains unclear, especially in polluted environments. In this study, we investigated the diurnal chemical compositions and formation processes of OA in carbonaceous particles during winter in Beijing using aerosol time-of-flight mass spectrometry. We found that 84.5% of the measured carbonaceous particles underwent aging processes, characterized by larger diameter and more secondary species compared to fresh carbonaceous particles, and presented different chemical compositions of OA in the daytime and nighttime. During the day, under high O3 concentrations, organosulfates and oligomers existed in the aged carbonaceous particles, which were mixed with a higher signal of nitrate compared with sulfate. At night, under high relative humidity, distinct spectral signatures of hydroxymethanesulfonate and organic nitrogen compounds, and minor signals of other hydroxyalkylsulfonates and high molecular weight organic compounds were present in the aged carbonaceous particles, which were mixed with a higher signal of sulfate compared with nitrate. Our results indicated that photochemistry contributed to OA formation in the daytime, while aqueous chemistry played an important role in OA formation in the nighttime. The findings can help improve the performance of air quality and climate models on OA simulation. Graphical abstract: Image 1 Highlights: Carbonaceous particles showed distinct diurnal chemical compositions of OA. Daytime photochemistry promoted the formation of organosulfates and oligomers. Nocturnal aqueous chemistry promoted the formation of hydroxyalkylsulfonates.